Systematic review and meta-analysis of the effect of zinc on wound healing - Nazanin Zand; Elena Arribas Lopez; Omorogieva Ojo; Tony Kochhar (BMJ Nutrition, Prevention & Health)
In times of metabolic stress, the demand for nutrients increases, which is essential to prevent delayed healing and development of chronic wounds. This study presents a systematic review and meta-analysis examining the effect of zinc treatment on wound healing. The review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and included data from four electronic data bases. Five clinical trials met the inclusion criteria. The meta-analysis suggested that zinc treatment may be associated with improvements in ulcers healing at the final endpoint MD: 1.41 (95% CI 1.04, 1.92, p = 0.03). Given the limitations of the included studies, a Grading of Recommendations, Assessment, Development and Evaluation assessment indicated a moderate quality of evidence.